Light attenuation in enriched purple phototrophic bacteria cultures: Implications for modelling and reactor design. (1st July 2022) - Capson-Tojo, Gabriel; Batstone, Damien J.; Grassino, Maria; Hülsen, Tim
Highlights: PPB absorb light at both NIR and VIS wavelengths. Light scattering did not affect attenuation. Pigments contributed considerably to attenuation via light absorption. The proposed model (based on Lambert-Beer) represented PPB growth accurately. Light penetration of 5 cm in concentrated cultures (≥600 g VS·m −3 ). Abstract: Light attenuation in enriched purple phototrophic bacteria (PPB) cultures has not been studied, and its understanding is critical for proper process modelling and reactor design, especially for scaled systems. This work evaluated the effect of different biomass concentrations, reactor configurations, wastewater matrices, and growth conditions, on the attenuation extent of near infra-red (NIR) and ultraviolet-visible (UV–VIS) light spectra. The results show that increased biomass concentrations lead to higher light attenuation, and that PPB absorb both VIS and NIR wavelengths, with both fractions of the spectrum being equally absorbed at biomass concentrations above 1, 000 g COD·m −3 . A flat plate configuration showed less attenuation compared with cylindrical reactors illuminated from the top, representative for open ponds. Neither a complex wastewater matrix nor the presence of polyhydroxyalkanoates (under nutrient limited conditions) affected light attenuation significantly. The pigment concentration (both bacteriochlorophyll and carotenoids) however, had a strong effect, with significant attenuation in the presence of pigments. Attenuation predictions using the Lambert-Beer law (excluding scattering) and the Schuster model (including scattering) indicated that light scattering had a minimal effect. A proposed mathematical model, based on the Lambert-Beer law and a Monod function for light requirements, allowed effective prediction of the kinetics of photoheterotrophic growth. This resulted in a half saturation coefficient of 4.6 W·m −2 . Finally, the results showed that in dense outdoor PPB cultures (≥1, 000 g COD·m −3 ), effective light penetration is only 5 cm, which biases design away from horizontal lagoons, and towards non-incident multi-panel systems such as flat plate reactors. Graphical abstract: Image, graphical abstract